Communication of genetic information in Filipino families affected with congenital adrenal hyperplasia - Abad, Peter James Bongolan; Abad, Peter James Bongolan (Manila College of Nursing, University of the Philippines Manila, 2015)
Congenital adrenal hyperplasia (CAH), like other genetic conditions, is a relational disease from both the biological and psychosocial point of views. A variety of health and reproductive implications may arise among biologically-related family members given the diagnosis of a genetic condition. Furthermore, a genetic condition can also influence psychosocial functioning, coping patterns, and the over-all dynamics of the family. It is in these contexts that the process of communicating genetic information in families is important to study. Unraveling how communication occurs in a family may guide genetic counselors in providing support to individuals and their relatives. Hence, the goal of this study is to explore communication of genetic information in Filipino families affected with CAH. -- A qualitative descriptive design was used for this study. Volunteer families with a child affected with CAH recruited through the CAH parent support group were interviewed. The semi-structured interviews explored flow and content of genetic information communicated in the family, the meanings the families attached to the communicated information, and the motivating and hindering factors in communication. An informative genogram was also drawn for each family to visually represent the flow of genetic information communication. The findings were analyzed using Interpretative Phenomenological Analysis (IPA). -- A total of five families participated, with includes 11 individuals. Findings revealed that the diagnosis of CAH is not kept secret and it is openly shared with the family including non-relatives like friends and neighbors. The decision to communicate seemed to be influenced by a number of factors including the family's desire to seek further information about their family history. Initially, the focus of the communicated information is on the health implications and while communication about genetics of the condition also occurs, this is almost always confines to the immediately family only. In the process of communication, the mother serves the roles of primary communicator in the family. The families have limited understanding of congenital adrenal hyperplasia especially its genetic implications including recurrence risk and carrier status. In an effort to understand more the condition, the family engages in an educative process that involved searching for additional information about the condition using other sources of information like the internet and social media. -- The findings of the study provide guidance to genetic counselors on how they can support families as they communicate information about congenital adrenal hyperplasia with the rest of their family.
Thesis (Master of Science in Genetic Counseling)
Keywords: Adrenogenital Syndrome; Communication -- General Counseling